Indonesia : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Indonesia. (IMF Staff Country Reports; Country Report, 2017)
This 2016 Article IV Consultation highlights that Indonesia has maintained macroeconomic stability, while adjusting well to recent shifts in the external environment. A prudent mix of macroeconomic policies and the launch of structural reforms have helped the economy weather slow global growth, the commodity down cycle, and several episodes of financial turbulence affecting emerging market economies. Growth in 2016 is projected at 5 percent on account of robust private consumption. In 2017, growth is expected to rise modestly to 5.1 percent, led by a gradual pickup in private investment in response to stronger commodity prices, low interest rates, and a recovery in external demand on the back of a pickup in global growth and trade.